A new genus, Zeoliarus, for the endemic New Zealand species Oliarus atkinsoni Myers and O. oppositus (Walker) (Hemiptera: Fulgoromorpha: Cixiidae: Cixiinae: Pentastirini) - Larivière, Marie-Claude; Fletcher, Murray J. (Zootaxa, 2008)
The New Zealand cixiid planthoppers were revised by Larivière (1999) who noted that further systematics work was required on a world basis or at least in an Australasian context before the position of New Zealand genera could be determined. As a consequence, most existing generic concepts were accepted by Larivière (1999), including the placement of two species in Oliarus Stål, 1862, a well-known catch-all pentastirine genus with species from all over the world.